Design pedagógico em ambientes digitais: perspectivas de análise para o campo da alfabetização e letramento - Marcia Helena Mesquita Ferreira (2011)
The present research had as a proposition for its development the problematizing of the term pedagogical design and its applying to the formative processes. It is a documental research based on the analysis of the pedagogical design of the digital media developed by the academic field, setting as the target children in the beginning of literacy. The application the term pedagogical design was structured in three analytical perspectives: media as digital image(based on the studies proposed by the Grammar of Visual Design of Kress and Van Leeuwen), the media in its own functionalities, andthe media in its pedagogical composition. As study objects we have selected two media developed by researches carried in pos-graduation programs, that have counted on fostering by public agencies specify for its development. From the data presented by the referred media devices we have verified the preoccupation of the academic field concerning the development of epistemologically based media, even though they do not have in its structuring the exploration of the resources available and applicable to the child public, in special children that do not have yet the mastering of the written code.